Azimuthal dependence of two-particle transverse momentum current correlations - Niseem Magdy; Sumit Basu; Victor Gonzalez; Ana Marin; Olga Evdokimov; Roy A. Lacey; Claude Pruneau (European Physical Journal C: Particles and Fields, 2021)
Abstract Two-particle transverse momentum correlation functions are a powerful technique for understanding the dynamics of relativistic heavy-ion collisions. Among these, the transverse momentum correlator $$G_{2}\left( \varDelta η ,\varDelta φ \right) $$ G 2 Δ η , Δ φ is of particular interest for its potential sensitivity to the shear viscosity per unit of entropy density $$η /s$$ η / s of the quark-gluon plasma formed in heavy-ion collisions. We use the UrQMD, AMPT, and EPOS models for Au–Au at $$\sqrt{s_NN}$$ s NN = 200 GeV and Pb–Pb at $$\sqrt{s_NN}$$ s NN = 2760 GeV to investigate the long range azimuthal dependence of $$G_{2}\left( \varDelta η ,\varDelta φ \right) $$ G 2 Δ η , Δ φ , and explore its utility to constrain $$η /s$$ η / s based on charged particle correlations. We find that the three models yield quantitatively distinct transverse momentum Fourier harmonics coefficients $$a^{p_T}_{n}$$ a n p T . We also observe these coefficients exhibit a significant dependence on $$η /s$$ η / s in the context of the AMPT model. These observations suggest that exhaustive measurements of the dependence of $$G_{2}\left( \varDelta φ \right) $$ G 2 Δ φ with collision energy, system size, collision centrality, in particular, offer the potential to distinguish between different theoretical models and their underlying assumptions. Exhaustive analyses of $$G_{2}\left( \varDelta φ \right) $$ G 2 Δ φ obtained in large and small systems should also be instrumental in establishing new constraints for precise extraction of $$η /s$$ η / s .